Discurso político-eleitoral da campanha presidencial no primeiro turno do ano 2002: uma análise discursiva da promessa e da crítica - Maria Aparecida Silva Furtado (2004)
Our dissertation proposes an analysis of the political and electoral speech that is composed by the speeches of the six candidates to the Presidency of Brazil in the election of the first turn 2002. We believe that the knowledge of the conditions of the formation of these speeches may be useful to the understanding of the discursive facts both in the theory and in their working in the society. This work consists of five important parts. In the first chapter, we have the general theoretical and methodological features, which structures this research. Next, the second chapter is made of theoretical fundaments of the Discursive Formation, Theory of the Enunciation, Semiolinguistics Theory, and Theory of the Acts of Speech, used in the development of this paper. The data of the corpus of this research are analysed in the third chapter, from the underlined theories and for the purpose of characterising the political and electoral speech. In the fourth chapter, we underline basing on the Theory of the Acts of Speech, the analysis of two purposes of such speech: the promise and the critics. And, at last, in the conclusion, the analytical results of the study as well as new perspectives of this research are presented.